Analysis Readiness And Strategy Of Human Resource Management In Hospitals In Face Global Health Crisis : A Literature Review Covid-19 Pandemic - Davina Aisha (CV. AFDIFAL MAJU BERKAH, 2026)
Appropriate​ with objective House created pain​ For increase quality life someone , house Sick naturally must own readiness in face various type challenge health , one of them is crisis global health . The COVID-19 pandemic that occurred a number of year Then is one of the example crisis global health that has a huge impact for system health throughout the world, especially in management Human Resources ( HR ) at home sick . Review matter said , the study literature This done For analyze HR management readiness and strategy at home Sick in face crisis global health , especially during the COVID-19 pandemic . This article arranged with method literature review sourced from from a number of study previous research​ the Then will reviewed and carried out identification related approach strategic , challenges in strategy implementation , as well as a number of learning that can be taken from various context geographical . Literature results show that part big House Sick experience gap between needs and availability power health , as well as pressure sufficient psychological​ high . In addition factor other like limitations training as well as facilities and infrastructure also become A obstacle . This study emphasize importance policy health human resource management that is adaptive , sustainable and responsive to crisis global health . This done so that the house Sick can maintain essential services​ as well as can guard welfare power health in the future come .